2018
DOI: 10.1111/jgh.14318
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Elective Diagnostic Procedure Complications: A Multicenter Cohort Analysis

Abstract: Ambulatory pediatric endoscopy is safe; significant adverse outcomes are rare but more likely in female, non-White or Hispanic patients and in patients with significant chronic comorbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…One large single center study of 9577 pediatric endoscopic procedures demonstrated a rate of adverse events (resulting in an unexpected hospital admission or medical intervention) of 0.26% following diagnostic procedures (6). Therapeutic procedures inherently carry a higher risk of adverse events with incidence varying with the procedure performed (6)(7)(8), with endoscopic dilatation, foreign body removal, and variceal ablation procedures more likely associated with adverse events (7).…”
Section: Discussionmentioning
confidence: 99%
“…One large single center study of 9577 pediatric endoscopic procedures demonstrated a rate of adverse events (resulting in an unexpected hospital admission or medical intervention) of 0.26% following diagnostic procedures (6). Therapeutic procedures inherently carry a higher risk of adverse events with incidence varying with the procedure performed (6)(7)(8), with endoscopic dilatation, foreign body removal, and variceal ablation procedures more likely associated with adverse events (7).…”
Section: Discussionmentioning
confidence: 99%
“…Much of the previous data on endoscopic AEs is derived from adult patients and may not be applicable to pediatrics 2,3 . Previous studies report a wide range of AE rates between 0.06% and 42% 4–12 . In 2010 the American Society for Gastrointestinal Endoscopy (ASGE) published terminology with regard to endoscopic AEs 13 .…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Previous studies report a wide range of AE rates between 0.06% and 42%. [4][5][6][7][8][9][10][11][12] In 2010 the American Society for Gastrointestinal Endoscopy (ASGE) published terminology with regard to endoscopic AEs. 13 However, these definitions include events that are less common in the pediatric population (i.e., myocardial infarction, cerebrovascular events, deep vein thrombosis).…”
mentioning
confidence: 99%
“…Events were more frequent in those less than 5 years of age and in those with obesity or lower respiratory disease. Lastly, a study of 217,817 children undergoing endoscopy which utilized the Pediatric Health Information System (PHIS) database found that 0.05% were admitted to the hospital and that 0.60% of patients presented to the emergency department following elective endoscopy [20]. One-half of these were for gastrointestinal symptoms.…”
Section: Introductionmentioning
confidence: 99%